The Effect of Story Reading Activities Media of Big Book on Interest in Reading and the Ability to Retell Early Childhood - Hikmah, Desy Athiyah Ali; Sukartiningsih, Wahyu; Purwoko, Budi (International Journal for Educational and Vocational Studies, 2019)
This study aims to determine the effect of story reading activities with big book media on reading interest and the ability to retell children aged 5-6 years. The research subjects were children aged 5-6 years at RA Al-kalam Surabaya. The research approach used is a quantitative approach with a quasi experimental design. The study data obtained through observation and documentation taken at the time of the study. Data analysis techniques in this study used an independent sample t-test. The results of data analysis show sig. 0.000 > 0.050, it shows that the null hypothesis is rejected so that it can be concluded that there is an effect of story reading activities using the big book media on reading interest and the retelling of children aged 5-6 years.